Sports marketing is an economic and strategic lever to promote brands in light of contemporary media - Berbache, Noureddine; Nadir, Bouslah; Benredjem, Ahmed; Mendjhi, Makhlouf; Benelbar, Said; Boubakre, Nouiri (Journal of Ecohumanism, 2026)
This theoretical-analytical study aims to explore the interactive relationship between contemporary media and sports marketing as economic and strategic levers to promote sports brands in the digital age. The study was based on the main hypothesis that the integration of media and communication with sports marketing contributes to raising the effectiveness of marketing campaigns and enhancing the mental image and brand loyalty. The study relied on a descriptive-analytical approach. To analyze the relevant literature and theoretical models, it relied on an approach that integrates economic and communication perspectives to understand how digital media, sports sponsorship, and event marketing and sports stars are used to build brand identity, market value, and sentiment. The results concluded that contemporary media, with its traditional and digital media, is no longer just a channel for transmitting the sporting event, but has become a strategic partner in the sports marketing industry by creating sustainable public interaction that enhances loyalty and belonging. It also showed that sponsorship and sports advertising supported by effective media coverage achieve higher marketing returns than traditional advertising, and that the integration between media and marketing generates a synergistic effect that exceeds the total impact of each individual element. The study concluded with proposing an interpretive theoretical model that integrates three main approaches: media, marketing, and the result of promoting the brand through awareness, mental image, and loyalty, making sports marketing supported by media a strategic lever to enhance the economic and social value of brands.